ON THE RUGGED PATH OF PROGRESS: CONTRIBUTIONS TO THE HISTORY OF RAILWAY ACCIDENTS IN COSTA RICA AND ANALYSIS OF CASES AT THE NORTHER RAILWAY COMPANY (1920-1940) - Sánchez Lovell, Adriana (2022)
The design and construction of transport routes in Costa Rica during the 19th century was mainly for agro-exports. In this way, the railways to the Pacific and the Caribbean met the objective of communicating coffee-producing areas (initially in the Central Valley) and, later, bananas (in the Costa Rican Caribbean), with the main ports of the country. Secondly, from the planning point of view, the issue of passenger transport is integrated. And while the Atlantic Railroad tried to renegotiate this matter, the contract with the company stipulated that they should provide passenger transport. This article analyzes some of the railway accidents that occurred between 1920 and 1940. This is because after the construction of the railway, there were a number of changes in the location of the tracks, depending on the abandonment of land due to plagues and possibly social movements. Most of the cases that are addressed, are of passengers of the train or of pedestrians that were beaten or run over by the machine, because the objective of this work lies in explaining some human and sociocultural factors, involved in the participation in railway accidents, from the casuistry.